Fabrication of dense b-calcium orthophosphate with submicrometer-sized grains and its high-temperature superplastic deformation - Watanabe, D.; Nishio, K.; Sakka, Y.; Ohgaki, M.; Davies, Ian; Umeda, T.; Koda, S.; Itatani, K. (Springer, 2011)
High-density b-calcium orthophosphate (b-Ca3(PO4)2, also called b-tricalcium phosphate: b-TCP)ceramics with submicrometer-sized grains were fabricated using a pulse-current pressure firing route. The maximum relative density of the b-TCP compacts was 98.7% at 1050 C and this was accompanied by a translucent appearance. The mean grain size of the b-TCP compacts increased slightly with temperature to reach 0.78 lm at 1000 C. However, upon further increasing the firing temperature to 1050 C the mean grain size increased significantly to 1.6 lm. The extent of plastic deformation during tensile testing was examined at temperatures between 900 and 1100 C using a strain rate in the range 9.26 9 10-5 to 4.44 9 10-4 s-1. The maximum tensile strain achieved was 145% for a test temperature of 1000 C and strain rate of 1.48 9 10-4 s-1 and this was attributedto the relatively high density and small grain size.